2013 IEEE International Conference on Acoustics, Speech and Signal Processing 2013
DOI: 10.1109/icassp.2013.6638911
|View full text |Cite
|
Sign up to set email alerts
|

MEMS-based inertial navigation based on a magnetic field map

Abstract: This paper presents an approach for 6D pose estimation where MEMS inertial measurements are complemented with magnetometer measurements assuming that a model (map) of the magnetic field is known. The resulting estimation problem is solved using a RaoBlackwellized particle filter. In our experimental study the magnetic field is generated by a magnetic coil giving rise to a magnetic field that we can model using analytical expressions. The experimental results show that accurate position estimates can be obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Although the idea has been around for a while (see e.g. [10], [11] for early results), only recently it has attracted the interest of many research groups [5], [12], [13], [14], [15]. In our earlier work we have shown that an indoor magnetic field contains enough information (Fig.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the idea has been around for a while (see e.g. [10], [11] for early results), only recently it has attracted the interest of many research groups [5], [12], [13], [14], [15]. In our earlier work we have shown that an indoor magnetic field contains enough information (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Often in estimation one has to rely heavily on predictive models, such as Gaussian Processes (GP) [6], to for example interpolate and extrapolate map values in unmeasured areas [4], [5]. If the available data is scarce or the models inaccurate, the estimates may contain considerable estimation errors, especially when extrapolating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanic tracking systems as described above can hence not be used due to their limited region of operation. Also, magnetic tracking such as [75] is excluded because of the same reason.…”
Section: Pose Estimation In Room-scaled Environmentsmentioning
confidence: 99%
“…Magnetometers, in combination with odometry, have also been shown to be a viable option for indoor simultaneous localization and mapping (SLAM) for robots [11], [12] as well as humans [12], [13]. Finally, location tracking by using magnetometers and MEMS inertial measurements based on a priori known maps was proposed in [14]. However, fusion of the accelerometer and magnetometers for vehicle trajectory estimation under the above mentioned circumstances is a novel approach.…”
Section: Introductionmentioning
confidence: 99%